Retrofitting the easy way thanks to new set of ICT tools. (Research'eu results magazine)
Energy-efficient retrofitting may be a market with much potential, but the current lack of tools for comparing available technologies and putting customers in touch with specialised SMEs is hampering its growth. The NEWBEE project has come up with innovative solutions to these two problems.